Plasma waves in the very local interstellar medium: a brief review - Kurth, W. S.; Granroth, L. J. (My University, 2023)
The Plasma Wave Science instruments on the two Voyager spacecraft are providing observations of plasma waves in the very local interstellar medium. One of the most important aspects of these observations are the inferred electron densities from the identification of electron plasma oscillations and a quasi-thermal line at the plasma frequency. They provide the first and only in situ determination of the plasma density in the interstellar medium and have revealed an outward radial gradient as a large scale feature of the interstellar medium upstream of the heliopause. The presence of the electron plasma oscillations provides evidence that transients from the sun, after propagating through the heliosphere, can modulate the surrounding medium.
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED